2004
DOI: 10.1016/j.virol.2003.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Avian reovirus σC protein induces apoptosis in cultured cells

Abstract: The avian reovirus (ARV) infection is associated with various disease conditions in poultry. However, the pathogenesis mechanisms are poorly characterized. In the present study, we clearly demonstrated that the sigmaC of ARV S1133 strain induced apoptosis in both BHK-21 and Vero cells. Five kinds of assays for apoptosis were used in analyzing ARV-infected BHK-21 and Vero cells: (1) assay for DNA ladders, (2) ELISA detection of cytoplasmic histone-associated DNA fragments, (3) nuclear staining with acridine ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
75
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 47 publications
7
75
0
Order By: Relevance
“…Although ARV causes caspase-dependent apoptosis (8,33,51), ARV p17 does not induce apoptosis (34), suggesting involvement of a different mechanism. During the G 2 /M phases of the cell cycle, eIF4E is dephosphorylated leading to blockage of formation of the eIF4F complex and reducing the magnitude of cap-dependent translation.…”
mentioning
confidence: 99%
“…Although ARV causes caspase-dependent apoptosis (8,33,51), ARV p17 does not induce apoptosis (34), suggesting involvement of a different mechanism. During the G 2 /M phases of the cell cycle, eIF4E is dephosphorylated leading to blockage of formation of the eIF4F complex and reducing the magnitude of cap-dependent translation.…”
mentioning
confidence: 99%
“…6 In mammals, there is an excellent correlation between the location of virus infection, the presence of tissue injury, and apoptosis, indicating that apoptosis is a critical mechanism by which disease is triggered in the host. 6 Mammalian 6 and avian 18,41 reovirus-induced apoptosis has been well documented, and it has been suggested that bystander apoptosis could result from the release of tumor necrosis factorrelated apoptosis-inducing ligand (TRAIL) or other death ligands from reovirus-infected cells. 6 In this study, apoptosis was present not only in virus antigen-positive cells of the bursa and spleen, but also in cells that were negative for viral staining, like lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the nonstructural protein p17 is reported to regulate the cell cycle and host cellular translation (24). The avian reovirus fiber is formed by capsid protein C and is encoded by the third open reading frame of the S1 segment, which is responsible for host cell attachment (25,26) and induction of apoptosis (27).…”
mentioning
confidence: 99%
“…For the past several years, our laboratory has been studying molecular evolution of ARV and signaling pathways triggered by ARV required for apoptosis induction, virus replication, and cell cycle perturbations (22,(27)(28)(29)(30)(31)(32)(33). To date, the molecular events leading to endocytosis by ARV are still completely unknown.…”
mentioning
confidence: 99%